Impact of pulsed light on colour, carotenoid, polyacetylene and sugar content of carrot slices. (August 2017) - Aguiló-Aguayo, I.; Gangopadhyay, N.; Lyng, J.G.; Brunton, N.; Rai, D.K.
Abstract: Carrot slices were subjected to pulsed light (PL) treatments on both sides (total PL fluences of 2.26, 4.52, 5.41, 9.38 and 13.15 J/cm 2 ) with the objective to evaluate their effect on the colour, β-carotene, polyacetylene and soluble sugar content. Higher concentrations of β-carotene were found after processing of carrot slices to the fluences of 2.26 and 4.52 J/cm 2 as compared with untreated carrots. This behaviour was partly related to the strongly colour observed in the cortex tissue of samples when similar PL treatment conditions were applied. Moreover, carrot slices treated with PL doses of 2.26 J/cm 2 also showed the highest falcarindiol (127.1%), falcarinol (94.8%) and falcarindiol-3-acetate (84.7%) retention levels. The same PL dose also led to an increment in the β-glucose in carrot slices after the treatment. Industrial relevance: The pre-treatment of carrot slices with pulsed light would enhance the level of polyacetylene and carotenoid content as a stress response without affecting negatively the colour characteristics of the fresh material. Pulsed light technology could be useful for the food industry in production of high value phytochemical vegetable products. Highlights: Increase in luminosity of peripheral cortex was observed when applying fluences up to 5.41 J/cm 2 . PL fluences of 2.26 J/cm 2 promoted enhancement of β-carotene and falcarindiol in carrot slices. Increment in β-glucose and α-glucose in carrot slices was observed after applying of 2.26 J/cm 2 .